Planning for the Management of A Boarding School Based Flagship School Program at SMA Negeri Taruna Kasuari Nusantara Papua Barat - Muhammad Arizal Ikhsan Matoka,; Yeri Sutopo, (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to analyze the management planning of boarding school-based flagship school programs at SMA Negeri Taruna Kasuari Nusantara, West Papua. The background of this research is based on the need to integrate academic education, character development, and discipline through 24-hour structured activities that support the formation of characterful, independent, and competitive students. The research uses a qualitative approach with case studies, involving observation, interviews, and documentation as primary and secondary data sources. Data analysis was carried out through reduction, presentation, and conclusion drawn, and validity was tested using credibility, transferability, dependability, and confirmability. The results of the study show that planning at SMA Taruna Kasuari Nusantara is carried out systematically and participatory, involving the Education Office, school principals, teachers, dormitory coaches, and TNI partners. Planning includes the preparation of vision-mission, educational calendar, academic and non-academic schedules, character education base periods, mandatory extracurricular activities, and student life regulations (PERDUPSIS). Students' daily activities are designed to balance academics, worship, physical exercise, and character building. Despite the limitations of facilities and educators, government support through budgets and infrastructure is a key factor in the sustainability of the program. Overall, this planning management has succeeded in integrating goals, activities, and character values, so that it is expected to produce graduates who are faithful, disciplined, responsible, with leadership character, love for the homeland, and competitive in the global era. Keywords: Planning, Management of Boarding School, Flagship School Program.